Analysis of Quality Control to Reduce Defective Products for Dry Syrup Using Six-Sigma Method in PT XYZ - et. al., Neng Sri Triana, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Quality control is an activity to ensure the level of quality of any product in accordance with the specifications that have been set. PT XYZ is a manufacture industry engaged in pharmaceuticals, where companies are required to produce high quality products, because it is used for medicinal purposes. Defective products produced was as much as 6.01% exceeded the requirements of the company of 3.0%. This study used the six sigma method: define, measure, analyze, improve, control. Through this method, it can be determined that sigma value is amounted to 3.06 with 60.264.13 DPMO. At the analyze stage, the causative factors of damage were successfully obtained, including humans, materials, methods, and machines, where human factor became an important factor in this study. Defective products can be produced due to workers experiencing carelessness due to work fatigue. The method used to measure work fatigue were descriptive observational and chi square collation tests to determine the relationship to the factors causing fatigue. The results showed that there is a relationship of age and work period factors with work fatigue. Moreover, the results of this study are able to provide sigma value recommendations as well as improvement measures to reduce defective products during the production process.